FRI0417 Comparison of Clinical and Serological Manifestations among Juvenile-, Adult-, and Late-Onset Systemic Lupus Erythematosus Patients in Korea. (10th June 2014) - Lee, K.-E.; Lee, J.-W.; Wen, L.; Park, D.-J.; Kim, T.-J.; Lee, S.-S.
Abstract : Background: Up to 30-40% of patients with systemic lupus erythematosus (SLE) experience their onset prior to adulthood or at over 50 years of age. Patients with juvenile-onset SLE (JSLE) frequently present with severe organ involvement and higher disease activity at the onset of disease. In contrast, patients with late-onset SLE (LSLE) tend to show more insidious onset and mild initial clinical manifestations. However, few studies have investigated differences in clinical manifestations with disease onset in Asian lupus patients. Objectives: Thus, we investigated whether SLE patients could be distinguished based on the time of disease onset and, if so, whether the groups differed in their clinical and laboratory features in ethnically homogeneous Korean patients. Methods: We enrolled 201 SLE patients (mean age 34.1±12.7, 184 women) with available clinical data at the time of onset of SLE from the lupus cohort at Chonnam National University Hospital. Sociodemographic, clinical, and laboratory data, including autoantibodies, and concomitant diseases were found at the time of diagnosis of SLE by reviewing the patient charts. We divided SLE patients according to age at SLE diagnosis into three groups: JSLE (diagnosed at ≤18 years), adult-onset SLE (ASLE, diagnosed at 19-50 years), and LSLE (diagnosed at >50 years), and compared baseline demographic, clinical, and relevant laboratory findings. Data were analyzed using the chi-squared test for categorical variables and one-way ANOVA test for continuous variables. Results: Of the 210 patients, 27 (14.4%), 149 (74.1%), and 25 (12.4%) were JSLE, ASLE, and LSLE patients, respectively. Fever, oral ulcer, nephritis, anemia, and thrombocytopenia were more common in JSLE patients than ASLE or LSLE patients (p<0.05, p<0.05, p=0.001, p<0.05, and p<0.05, respectively). On the other hand, Sjögren's syndrome was found more frequently in LSLE patients than JSLE or ASLE patients (p<0.05). SLEDAI-2000 scores at the onset of SLE were 14.6±7.1 in JSLE, 11.1±6.1 in ASLE, and 6.6±2.7 in LSLE, and disease activity was significantly higher in JSLE patients than in ASLE or LSLE patients (p<0.001). Anti-dsDNA and anti-nucleosome antibodies were found more frequently in JSLE patients and less frequently in LSLE patients (p<0.05, p=0.005) and decreased complement levels (C3, C4, and CH50) were more common in JSLE patients and less common in LSLE patients (p<0.001, p<0.001, and p<0.05, respectively). Conclusions: Our results showed that SLE patients present with different clinical and serological manifestations according to age at disease onset. JSLE patients have severe disease activity and more frequent renal involvement and LSLE patients have mild disease activity, more commonly accompanied by Sjögren's syndrome, at disease onset. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2686